Ultralow-hardness Australian-standard low-smoke halogen-free high-flame-retardant polyolefin cable material and preparation method thereof

By using low-hardness EVA resin and ultra-low hardness polyethylene elastomer in polyolefin cable materials, combined with special maleic anhydride grafting materials and homemade carbon synergistic agents, the problem of insufficient hardness and aging performance of traditional products is solved. It achieves high flame retardant and excellent Australian standard cable performance.

CN119144079APending Publication Date: 2024-12-17SUZHOU HENGLI COMM MATERIAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411268821.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Traditional low-smoke, halogen-free flame-retardant polyolefin cable materials cannot meet the hardness and aging requirements in the development of Australian standard soft cable outer sheath, resulting in difficult to meet thermal deformation and poor combustion performance.

Method used

Low-hardness EVA resin and ultra-low hardness polyethylene elastomer are used as the matrix, combined with special maleic anhydride grafting material, homemade carbon synergist and inorganic flame retardant, and made by refining-twin screw extrusion-single screw Preparation of ultra-low hardness Australian standard low smoke halogen-free high flame retardant polyolefin cable materials by particle technology.

Benefits of technology

It achieves high flame retardant performance, ultra-low hardness and excellent aging performance, meets the hardness and heat deformation requirements of Australian standard cables, and passes bundled C-level combustion and 110℃*480h aging detection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005038039760000011
    Figure BDA0005038039760000011
  • Figure FDA0005038039750000011
    Figure FDA0005038039750000011
Patent Text Reader

Abstract

The invention belongs to the field of polyolefin cable materials, and particularly relates to an ultralow-hardness Australian-standard low-smoke halogen-free high-flame-retardant polyolefin cable material and a preparation method thereof. The halogen-free flame-retardant polyolefin cable material with ultralow hardness, high flame retardance and better aging performance is developed for Australian standard cables with special requirements, 30-40 parts of ethylene-vinyl acetate copolymer (EVA) is added as a base material in the debugging process, and 20-30 parts of ultralow-hardness polyethylene octylene co-elastomer (POE) is added to endow the material with the ultralow hardness requirement; 15-20 parts of a special maleic anhydride grafting material ensures the overall compatibility and thermal deformation resistance of the material, and 1-2 parts of a lubricant improves the processing demolding performance and the surface glossiness of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polyolefin cable materials, and specifically relates to an ultra-low hardness Australian standard low-smoke halogen-free high flame retardant polyolefin cable material and a preparation method thereof. Background Art

[0002] Traditional low-smoke halogen-free flame-retardant polyolefin cable materials are based on polyolefin resins, with inorganic flame retardants (to improve the flame retardant properties of the resin), fillers (to reduce material costs), antioxidants (to improve the heat resistance of the product and delay aging), lubricants (to improve the processing performance of the product and make it easier for the material to be demolded and flowed) and other additives added in appropriate proportions and then mixed together through screw extrusion plasticization.

[0003] Current technical issues: This product is developed for the outer sheath of Australian standard soft cables, and conventional resins and aging systems cannot meet the hardness and aging requirements. And because the hardness requirements of this product are stringent, the problems caused by low hardness include difficulty in meeting thermal deformation requirements, and the inability to improve flame retardant filling, resulting in difficulty in meeting combustion performance requirements. Summary of the invention

[0004] In order to solve the above-mentioned technical problems, this application provides the following technical solutions:

[0005] The present invention provides an ultra-low hardness Australian standard low-smoke halogen-free high flame retardant polyolefin cable material, which comprises the following components by weight:

[0006]

[0007] The antioxidant is prepared by compounding three antioxidants, selected from antioxidant AT-10, antioxidant DLTP and antioxidant 1035 respectively;

[0008] The special maleic anhydride grafted material comprises polyethylene and SEBS, the grafting rate is not less than 0.7%, wherein the mass ratio of SEBS is 70%, the melting point is not less than 120°C, and the melting point of polyethylene is not less than 122°C;

[0009] The self-made carbon synergist is prepared from ethylene-vinyl acetate copolymer, montmorillonite, needle-shaped sepiolite and a dispersant through internal mixing and double-stage granulation.

[0010] Preferably, the content of vinyl acetate (VA) in the ethylene-vinyl acetate copolymer is not less than 28%.

[0011] Furthermore, the ethylene-vinyl acetate copolymer has a melt index of no more than 3.5 g / 10 min at 190° C. and a load of 2.16 kg.

[0012] Preferably, the ultra-low hardness polyolefin elastomer has a melt index of no more than 4 g / 10 min and a 15s hardness of no more than 50A at 190° C. and a load of 2.16 kg.

[0013] Preferably, the mass ratio of antioxidant AT-10, antioxidant DLTP and antioxidant 1035 is 3:2:1. Antioxidant AT-10 is manufactured by BASF; antioxidant DLTP is manufactured by Songyuan Baifu; antioxidant 1035 is manufactured by BASF.

[0014] Preferably, the inorganic flame retardant is selected from magnesium hydroxide and aluminum hydroxide; the mass ratio of the magnesium hydroxide to the aluminum hydroxide is 1:4.

[0015] Furthermore, the particle size D50 of the magnesium hydroxide is 1.8-2.5 μm. The oil absorption value of the aluminum hydroxide is ≤30 mL / 100 g.

[0016] Furthermore, the purity of the magnesium hydroxide is ≥99%.

[0017] Preferably, in the self-made carbon synergist, the dispersant is selected from ethylene bisstearamide, ethylene-vinyl acetate copolymer, montmorillonite, needle-shaped sepiolite and the mass ratio of the dispersant is 49:40:10:1.

[0018] Furthermore, during the banburying and two-stage granulation, the melt flow rate is 25 g / 10 min.

[0019] Furthermore, the needle-shaped sepiolite is of the brand CLAY-20, and the manufacturer is Zhuangjing Chemical.

[0020] Specifically, the dispersant is of brand B-50, and the manufacturer is Chaoyang Chemical.

[0021] The present invention also provides a method for preparing the above-mentioned ultra-low hardness Australian standard low-smoke halogen-free high flame retardant polyolefin cable material, comprising the following steps:

[0022] S1: Mixing and plasticizing the raw materials in an internal mixer to obtain processed materials;

[0023] S2: After the processed material is extruded through a twin-screw extruder, it is granulated through a single-screw extruder to obtain sheath raw material particles;

[0024] S3: conveying the sheath raw material particles through air cooling, and packaging to obtain the high tear resistance, low smoke, and halogen-free sheath material.

[0025] Preferably, the temperature of mixing and plasticizing in the internal mixer is 155-165°C, the temperature of extrusion in the twin-screw extruder is 105-115°C, and the temperature of granulation in the single-screw extruder is 110-150°C.

[0026] This product adopts the production process of internal mixer-twin screw mixing and plasticization, followed by single screw extrusion granulation, air cooling, conveying and packaging of the finished product.

[0027] The present invention develops a halogen-free flame-retardant polyolefin cable material with ultra-low hardness, high flame retardancy and better aging performance for Australian standard cables with special requirements. During the debugging process, 30-40 parts of ethylene-vinyl acetate copolymer (EVA) are tried to be added as a matrix material, 20-30 parts of ultra-low hardness polyethylene octene co-elastomer (POE) are added to give the material the requirement of ultra-low hardness, 15-20 parts of a special maleic anhydride grafted material ensures the overall compatibility and heat deformation resistance of the material, and 1-2 parts of a lubricant improves the processing demoulding performance and surface gloss of the material.

[0028] The technical solution of the present invention has the following advantages over the prior art:

[0029] The technology of the present invention develops halogen-free flame-retardant polyolefin cable materials with ultra-low hardness, high flame retardancy and better aging performance for Australian standard cables with special requirements.

[0030] The design idea of ​​this product is to use low-hardness EVA and POE resin as the main matrix, with special maleic anhydride grafted polyolefin, add inorganic flame retardant and self-made carbon synergist and other additives for blending and granulation. It can meet the requirements of Shore A hardness of 83±1, 90℃ heat deformation ≤50%, and the cable can pass the C-level burning and 110℃*480h aging. DETAILED DESCRIPTION

[0031] The present invention is further described below in conjunction with specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0032] Example 1

[0033] The ultra-low hardness Australian standard low-smoke halogen-free high flame-retardant polyolefin cable material of this embodiment is prepared by the following raw materials, by weight: 40 parts of ethylene-vinyl acetate copolymer (EVA), 40 parts of ultra-low hardness polyolefin elastomer (POE), 20 parts of special maleic anhydride grafted material, 115 parts of inorganic flame retardant, 5 parts of self-made carbon synergist, 1 part of antioxidant and 0.5 parts of alkoxy polysiloxane;

[0034] The antioxidant is prepared by mixing antioxidant AT-10, antioxidant DLTP and antioxidant 1035 in a mass ratio of 3:2:1;

[0035] The specially prepared maleic anhydride grafted material includes polyethylene and SEBS, with a grafting rate of not less than 0.7%, wherein the mass ratio of SEBS is 70%, the melting point thereof is not less than 120°C, and the melting point of polyethylene is not less than 122°C;

[0036] The self-made carbon synergist is prepared from ethylene-vinyl acetate copolymer, montmorillonite, needle-shaped sepiolite CLAY-20 and dispersant ethylene bisstearamide through internal mixing and two-stage granulation; during internal mixing and two-stage granulation, the melt flow rate is 25g / 10min.

[0037] The content of vinyl acetate (VA) in ethylene-vinyl acetate copolymer is not less than 28%. The melt index of ethylene-vinyl acetate copolymer is not more than 3.5g / 10min at 190℃ and load of 2.16kg; the melt index of ultra-low hardness polyolefin elastomer is not more than 4g / 10min at 190℃ and load of 2.16kg, and the hardness at 15s is not more than 50A.

[0038] The mass ratio of ethylene-vinyl acetate copolymer, montmorillonite, needle-shaped sepiolite and dispersant is 49:40:10:1.

[0039] The inorganic flame retardant is selected from magnesium hydroxide and aluminum hydroxide in a mass ratio of 1:4. The particle size D50 of the magnesium hydroxide is 2 μm. The oil absorption value of the aluminum hydroxide is ≤30 mL / 100 g. The purity of the magnesium hydroxide is ≥99%.

[0040] The preparation method of the above-mentioned ultra-low hardness Australian standard low-smoke halogen-free high flame retardant polyolefin cable material is as follows:

[0041] S1: Mix and plasticize the raw materials in an internal mixer at 160°C to obtain a processed material;

[0042] S2: extruding the processed material through a twin-screw extruder at 110° C., and then granulating through a single-screw extruder at 130° C. to obtain sheath raw material particles;

[0043] S3: The sheath raw material particles are conveyed and packaged by air cooling to obtain a high tear resistance, low smoke and halogen-free sheath material.

[0044] Example 2

[0045] The ultra-low hardness Australian standard low-smoke halogen-free high flame-retardant polyolefin cable material of this embodiment is prepared by the following raw materials, by weight: 30 parts of ethylene-vinyl acetate copolymer (EVA), 50 parts of ultra-low hardness polyolefin elastomer (POE), 20 parts of special maleic anhydride grafted material, 118 parts of inorganic flame retardant, 2 parts of self-made carbon synergist, 1.5 parts of antioxidant and 1 part of alkoxy polysiloxane;

[0046] The antioxidant is prepared by mixing antioxidant AT-10, antioxidant DLTP and antioxidant 1035 in a mass ratio of 3:2:1;

[0047] The specially made maleic anhydride grafted material includes polyethylene and SEBS, with a grafting rate of not less than 0.7%, wherein the mass ratio of SEBS is 70%, the melting point is not less than 120°C, and the melting point of polyethylene is not less than 122°C;

[0048] The self-made carbon synergist is prepared from ethylene-vinyl acetate copolymer, montmorillonite, needle-shaped sepiolite CLAY-20 and dispersant ethylene bisstearamide through internal mixing and two-stage granulation; during internal mixing and two-stage granulation, the melt flow rate is 25g / 10min.

[0049] The content of vinyl acetate (VA) in ethylene-vinyl acetate copolymer is not less than 28%. The melt index of ethylene-vinyl acetate copolymer is not more than 3.5g / 10min at 190℃ and load of 2.16kg; the melt index of ultra-low hardness polyolefin elastomer is not more than 4g / 10min at 190℃ and load of 2.16kg, and the hardness at 15s is not more than 50A.

[0050] The mass ratio of ethylene-vinyl acetate copolymer, montmorillonite, needle-shaped sepiolite and dispersant is 49:40:10:1.

[0051] The inorganic flame retardant is selected from magnesium hydroxide and aluminum hydroxide in a mass ratio of 1:4. The particle size D50 of the magnesium hydroxide is 2 μm. The oil absorption value of the aluminum hydroxide is ≤30 mL / 100 g. The purity of the magnesium hydroxide is ≥99%.

[0052] The preparation method of the above-mentioned ultra-low hardness Australian standard low-smoke halogen-free high flame retardant polyolefin cable material is as follows:

[0053] S1: Mix and plasticize the raw materials in an internal mixer at 160°C to obtain a processed material;

[0054] S2: extruding the processed material through a twin-screw extruder at 110° C., and then granulating through a single-screw extruder at 130° C. to obtain sheath raw material particles;

[0055] S3: The sheath raw material particles are conveyed and packaged by air cooling to obtain a high tear resistance, low smoke and halogen-free sheath material.

[0056] Example 3

[0057] The ultra-low hardness Australian standard low-smoke halogen-free high flame-retardant polyolefin cable material of this embodiment is prepared by the following raw materials, by weight: 45 parts of ethylene-vinyl acetate copolymer (EVA), 40 parts of ultra-low hardness polyolefin elastomer (POE), 15 parts of special maleic anhydride grafted material, 120 parts of inorganic flame retardant, 1 part of self-made carbon synergist, 1.5 parts of antioxidant and 1 part of alkoxy polysiloxane;

[0058] The antioxidant is prepared by mixing antioxidant AT-10, antioxidant DLTP and antioxidant 1035 in a mass ratio of 3:2:1;

[0059] The specially prepared maleic anhydride grafted material includes polyethylene and SEBS, with a grafting rate of not less than 0.7%, wherein the mass ratio of SEBS is 70%, the melting point thereof is not less than 120°C, and the melting point of polyethylene is not less than 122°C;

[0060] The self-made carbon synergist is prepared from ethylene-vinyl acetate copolymer, montmorillonite, needle-shaped sepiolite CLAY-20 and dispersant ethylene bisstearamide through internal mixing and two-stage granulation; during internal mixing and two-stage granulation, the melt flow rate is 25g / 10min.

[0061] The content of vinyl acetate (VA) in ethylene-vinyl acetate copolymer is not less than 28%. The melt index of ethylene-vinyl acetate copolymer is not more than 3.5g / 10min at 190℃ and load of 2.16kg; the melt index of ultra-low hardness polyolefin elastomer is not more than 4g / 10min at 190℃ and load of 2.16kg, and the hardness at 15s is not more than 50A.

[0062] The mass ratio of ethylene-vinyl acetate copolymer, montmorillonite, needle-shaped sepiolite and dispersant is 49:40:10:1.

[0063] The inorganic flame retardant is selected from magnesium hydroxide and aluminum hydroxide in a mass ratio of 1:4. The particle size D50 of the magnesium hydroxide is 2 μm. The oil absorption value of the aluminum hydroxide is ≤30 mL / 100 g. The purity of the magnesium hydroxide is ≥99%.

[0064] The preparation method of the above-mentioned ultra-low hardness Australian standard low-smoke halogen-free high flame retardant polyolefin cable material is as follows:

[0065] S1: Mix and plasticize the raw materials in an internal mixer at 160°C to obtain a processed material;

[0066] S2: extruding the processed material through a twin-screw extruder at 110° C., and then granulating through a single-screw extruder at 130° C. to obtain sheath raw material particles;

[0067] S3: The sheath raw material particles are conveyed and packaged by air cooling to obtain a high tear resistance, low smoke and halogen-free sheath material.

[0068] Example 4

[0069] The ultra-low hardness Australian standard low-smoke halogen-free high flame-retardant polyolefin cable material of this embodiment is prepared by the following raw materials, by weight: 30 parts of ethylene-vinyl acetate copolymer (EVA), 30 parts of ultra-low hardness polyolefin elastomer (POE), 15 parts of special maleic anhydride grafted material, 110 parts of inorganic flame retardant, 1 part of self-made carbon synergist, 1 part of antioxidant and 0.5 parts of alkoxy polysiloxane;

[0070] The antioxidant is prepared by mixing antioxidant AT-10, antioxidant DLTP and antioxidant 1035 in a mass ratio of 3:2:1;

[0071] The specially made maleic anhydride grafted material includes polyethylene and SEBS, with a grafting rate of not less than 0.7%, wherein the mass ratio of SEBS is 70%, the melting point is not less than 120°C, and the melting point of polyethylene is not less than 122°C;

[0072] The self-made carbon synergist is prepared from ethylene-vinyl acetate copolymer, montmorillonite, needle-shaped sepiolite CLAY-20 and dispersant ethylene bisstearamide through internal mixing and two-stage granulation; during internal mixing and two-stage granulation, the melt flow rate is 25g / 10min.

[0073] The content of vinyl acetate (VA) in ethylene-vinyl acetate copolymer is not less than 28%. The melt index of ethylene-vinyl acetate copolymer is not more than 3.5g / 10min at 190℃ and load of 2.16kg; the melt index of ultra-low hardness polyolefin elastomer is not more than 4g / 10min at 190℃ and load of 2.16kg, and the hardness at 15s is not more than 50A.

[0074] The mass ratio of ethylene-vinyl acetate copolymer, montmorillonite, needle-shaped sepiolite and dispersant is 49:40:10:1.

[0075] The inorganic flame retardant is selected from magnesium hydroxide and aluminum hydroxide in a mass ratio of 1:4. The average particle size D50 of the magnesium hydroxide is 1.8 μm. The oil absorption value of the aluminum hydroxide is ≤30 mL / 100 g. The purity of the magnesium hydroxide is ≥99%.

[0076] The preparation method of the above-mentioned ultra-low hardness Australian standard low-smoke halogen-free high flame retardant polyolefin cable material is as follows:

[0077] S1: Mix and plasticize the raw materials in an internal mixer at 155°C to obtain a processed material;

[0078] S2: extruding the processed material through a twin-screw extruder at 105° C., and then granulating through a single-screw extruder at 110° C. to obtain sheath raw material particles;

[0079] S3: The sheath raw material particles are conveyed and packaged by air cooling to obtain a high tear resistance, low smoke and halogen-free sheath material.

[0080] Example 5

[0081] The ultra-low hardness Australian standard low-smoke halogen-free high flame-retardant polyolefin cable material of this embodiment is prepared by the following raw materials, by weight: 50 parts of ethylene-vinyl acetate copolymer (EVA), 50 parts of ultra-low hardness polyolefin elastomer (POE), 20 parts of special maleic anhydride grafted material, 130 parts of inorganic flame retardant, 5 parts of self-made carbon synergist, 2 parts of antioxidant and 1 part of alkoxy polysiloxane;

[0082] The antioxidant is prepared by mixing antioxidant AT-10, antioxidant DLTP and antioxidant 1035 in a mass ratio of 3:2:1;

[0083] The specially prepared maleic anhydride grafted material includes polyethylene and SEBS, with a grafting rate of not less than 0.7%, wherein the mass ratio of SEBS is 70%, the melting point thereof is not less than 120°C, and the melting point of polyethylene is not less than 122°C;

[0084] The self-made carbon synergist is prepared from ethylene-vinyl acetate copolymer, montmorillonite, needle-shaped sepiolite CLAY-20 and dispersant ethylene bisstearamide through internal mixing and two-stage granulation; during internal mixing and two-stage granulation, the melt flow rate is 25g / 10min.

[0085] The content of vinyl acetate (VA) in ethylene-vinyl acetate copolymer is not less than 28%. The melt index of ethylene-vinyl acetate copolymer is not more than 3.5g / 10min at 190℃ and load of 2.16kg; the melt index of ultra-low hardness polyolefin elastomer is not more than 4g / 10min at 190℃ and load of 2.16kg, and the hardness at 15s is not more than 50A.

[0086] The mass ratio of ethylene-vinyl acetate copolymer, montmorillonite, needle-shaped sepiolite and dispersant is 49:40:10:1.

[0087] The inorganic flame retardant is selected from magnesium hydroxide and aluminum hydroxide in a mass ratio of 1:4. The particle size D50 of the magnesium hydroxide is 2.5 μm. The oil absorption value of the aluminum hydroxide is ≤30 mL / 100 g. The purity of the magnesium hydroxide is ≥99%.

[0088] The preparation method of the above-mentioned ultra-low hardness Australian standard low-smoke halogen-free high flame retardant polyolefin cable material is as follows:

[0089] S1: Mix and plasticize the raw materials in an internal mixer at 165°C to obtain a processed material;

[0090] S2: extruding the processed material through a twin-screw extruder at 115° C., and then granulating through a single-screw extruder at 150° C. to obtain sheath raw material particles;

[0091] S3: The sheath raw material particles are conveyed and packaged by air cooling to obtain a high tear resistance, low smoke and halogen-free sheath material.

[0092] Effect evaluation 1

[0093] The main performance parameters of Example 1 are as follows: tensile strength: 10.5MPa, low impact brittle temperature: -45℃, hardness: 83A, 90℃ thermal deformation: 15%, hardness: 1.35g / cm 3 , elongation at break: 550%, temperature resistance grade: 90℃, heat aging (110℃*20 days): strength and elongation change rate is less than 25%, and bundled C combustion passes the test standard.

[0094] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. An ultra-low hardness Australian standard low-smoke halogen-free high flame retardant polyolefin cable material, characterized in that: By weight, it includes the following components: The antioxidant is prepared by compounding three antioxidants, selected from antioxidant AT-10, antioxidant DLTP and antioxidant 1035 respectively; The special maleic anhydride grafted material comprises polyethylene and SEBS, the grafting rate is not less than 0.7%, wherein the mass ratio of SEBS is 70%, the melting point is not less than 120°C, and the melting point of polyethylene is not less than 122°C; The self-made carbon synergist is prepared from ethylene-vinyl acetate copolymer, montmorillonite, needle-shaped sepiolite and a dispersant through internal mixing and double-stage granulation.

2. The ultra-low hardness Australian standard low-smoke halogen-free high flame retardant polyolefin cable material as claimed in claim 1, characterized in that: The content of vinyl acetate in the ethylene-vinyl acetate copolymer is not less than 28%.

3. The ultra-low hardness Australian standard low-smoke halogen-free high flame retardant polyolefin cable material as claimed in claim 2, characterized in that: The ethylene-vinyl acetate copolymer has a melt index of no more than 3.5 g / 10 min at 190° C. and a load of 2.16 kg.

4. The ultra-low hardness Australian standard low-smoke halogen-free high flame retardant polyolefin cable material as claimed in claim 1, characterized in that: The ultra-low hardness polyolefin elastomer has a melt index of no more than 4 g / 10 min at 190° C. and a load of 2.16 kg, and a 15s hardness of no more than 50A.

5. The ultra-low hardness Australian standard low-smoke halogen-free high flame retardant polyolefin cable material as claimed in claim 1, characterized in that: The mass ratio of antioxidant AT-10, antioxidant DLTP and antioxidant 1035 is 3:2:

1.

6. The ultra-low hardness Australian standard low-smoke halogen-free high flame retardant polyolefin cable material according to claim 1, characterized in that: The inorganic flame retardant is selected from magnesium hydroxide and aluminum hydroxide; the mass ratio of the magnesium hydroxide to the aluminum hydroxide is 1:

4.

7. The ultra-low hardness Australian standard low-smoke halogen-free high flame retardant polyolefin cable material as claimed in claim 6, characterized in that: The particle size D50 of the magnesium hydroxide is 1.8-2.5 μm. The oil absorption value of the aluminum hydroxide is ≤30 mL / 100 g.

8. The ultra-low hardness Australian standard low-smoke halogen-free high flame retardant polyolefin cable material according to claim 1, characterized in that: In the self-made carbon synergist, the dispersant is selected from ethylene bisstearamide, and the mass ratio of ethylene-vinyl acetate copolymer, montmorillonite, needle-shaped sepiolite and dispersant is 49:40:10:

1.

9. A method for preparing the ultra-low hardness Australian standard low-smoke halogen-free high flame retardant polyolefin cable material according to any one of claims 1 to 8, characterized in that: The steps include: S1: Mixing and plasticizing the raw materials in an internal mixer to obtain processed materials; S2: After the processed material is extruded through a twin-screw extruder, it is granulated through a single-screw extruder to obtain sheath raw material particles; S3: conveying the sheath raw material particles through air cooling, and packaging to obtain the high tear resistance, low smoke, and halogen-free sheath material.

10. The preparation method according to claim 9, characterized in that: The mixing and plasticizing temperature of the internal mixer is 155-165℃, the extrusion temperature of the twin-screw extruder is 105-115℃, and the granulation temperature of the single-screw extruder is 110-150℃.